Transcatheter access route options for treatment of degenerated mitral valve prosthesis with a balloon‐expandable biological valve. Issue 6 (9th August 2013) - Schaefer, Ulrich; Frerker, Christian; Bader, Ralf; Schmoeckel, Michael; Busse, Cord; Kuck, Karl‐Heinz
<x xml:space="preserve">Abstract</x> Objectives There is an ongoing discussion if valve‐in‐valve implantations into failing mitral xenografts should be performed only via a transapical approach. Background In selected high‐risk patients, transcatheter valve implantation is an emerging therapy for degenerated mitral xenografts in need of repeated valve replacement. Methods Here we describe three different strategies to treat a failing mitral biological prosthesis (Carpentier Edwards S.A.V) by implantation of a SAPIEN‐XT valve, which was performed in three different patients. As access site, a transjugular/transseptal approach, a transfemoral/transseptal approach, and a transapical approach were chosen. Results With all three approaches, valve‐in‐valve implantation was successfully achieved. The acute hemodynamic effects were excellent and according to VARC there was no adverse event recorded during a 6 months follow‐up. Conclusions Feasibility of all three approaches is demonstrated and might be taken into consideration for treatment in various patients. © 2012 Wiley Periodicals, Inc.